2001
DOI: 10.1074/jbc.m008982200
|View full text |Cite
|
Sign up to set email alerts
|

Hypusine Is Required for a Sequence-specific Interaction of Eukaryotic Initiation Factor 5A with Postsystematic Evolution of Ligands by Exponential Enrichment RNA

Abstract: Hypusine is formed through a spermidine-dependent posttranslational modification of eukaryotic initiation factor 5A (eIF-5A) at a specific lysine residue. The reaction is catalyzed by deoxyhypusine synthase and deoxyhypusine hydroxylase. eIF-5A is the only protein in eukaryotes and archaebacteria known to contain hypusine. Although both eIF-5A and deoxyhypusine synthase are essential genes for cell survival and proliferation, the precise biological function of eIF-5A is unclear. We have previously proposed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 39 publications
5
74
0
3
Order By: Relevance
“…With respect to the functions of IP16s, it has been demonstrated that eIF5A is capable of binding to RNA (Xu and Chen, 2001). As for TCTP, it has been reported that TCTP interacts with the ribosome-associated proteins eEF1A and eEF1B and functions as a guanine nucleotide dissociation inhibitor (Cans et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the functions of IP16s, it has been demonstrated that eIF5A is capable of binding to RNA (Xu and Chen, 2001). As for TCTP, it has been reported that TCTP interacts with the ribosome-associated proteins eEF1A and eEF1B and functions as a guanine nucleotide dissociation inhibitor (Cans et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Hypusine is an amino acid that is formed post-translationally in a reaction involving the enzymes DHS and deoxyhypusine hydroxylase and the substrates NAD ϩ and spermidine and is unique to the protein eIF5A (40). Importantly, hypusine is required for the majority of functions of eIF5A that have been studied to date (41,42), including those relevant to cytokine-induced ␤ cell dysfunction (13). The relationship between cytokine signaling and incident ER stress (37,38) therefore led us to investigate whether DHS inhibition in the C57BLKS/J-db/db strain might lead to improved glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…SELEX procedures were generally performed as previously described (31,33,38). The oligonucleotide template was synthesized as a single-stranded 88-mer with the sequence 5Ј-GCGGAATTCTAATACGACTCACTATAGGG AACAGTCCGAGCC-N 30 -GGGTCAATGCGTCATA-3Ј, where the central N 30 represents random oligonucleotides based on equal incorporation of A, G, C, and T at each position.…”
Section: Methodsmentioning
confidence: 99%